Residential Irrigation System Rainfall Shutoff Devices - Michael D. Dukes; Dorota Z. Haman (EDIS)
This document is ABE325, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published July 2002.